Représentations socio-professionnelles et choix de la spécialisation : le cas de la filière vétérinaire rurale - Sylvain Dernat; Arnaud Siméone
This article shows how a specific social representation, in particular a socio-professional representation, helps explain the choice of specialization of students in higher education, beyond social and demographic criteria. To illustrate this, we investigated the issue of selecting food animal practice in French veterinary education, which has been facing a strong disaffection over the past years. The results of a quantitative survey (n = 533), using several methods, suggest that the curriculum, and in particular the in-service periods could have a crucial importance in shifting from a social representation to a professional representation. These results challenge student recruitment criteria and underline the importance of instructional design in building up social representations and career pathways.